In-vitro Investigation of Polyphenol-Rich Date (Phoenix dactylifera L.) Seed Extract Bioactivity - Hilary, Serene; Kizhakkayil, Jaleel; Souka, Usama; Al-Meqbaali, Fatima; Ibrahim, Wissam; Platat, Carine (Frontiers in Nutrition, 2021)
Date seeds are a by-product of the date fruit processing industry with minimal human use; however, they are a rich source of polyphenols with a range of potential biological properties. The current study investigates the cytotoxicity of date seed polyphenols against cancer cell lines, its ability to combat hyperglycemia, its antioxidant potential and its anti-adipogenic effect. The present work aimed to establish the usefulness of date seeds in the food industry as a functional ingredient. The anti-tumour activity of DSE was tested in a panel of cell lines such as MCF-7, MDA-MB-231, Hep-G2, Caco-2, and PC-3 by measuring cell viability and cleaved PARP. Lipid accumulation and effect on the differentiation of 3T3-L1 cells (adipocytes) were tested with date seed extract treatments. The influence of date seed polyphenols on glucose uptake was studied in 3T3-L1 cells and C2C12 cells (muscle cells). The antioxidant activity of the polyphenols from date seed products such as date seed extract (DSE), date seed powder (DSP), and date seeds fortified bread (DSB) was tested following in-vitro digestion to study their stability in the gastrointestinal milieu. DSE treatment resulted in significantly reduced viability in MCF-7 and Hep-G2 cells with 48-h treatments. Glucose uptake increased in the adipocytes with DSE treatments; moreover, it inhibited adipocyte differentiation and lipid accumulation. DSE decreased the expression levels of PPAR-γ, C/EBPα, adiponectin and upregulated GLUT-4, and phospho-AMPK. This study also found that date seed samples retained antioxidant activity in the digestive milieu and concludes that the date seed polyphenols remain active in the digestive milieu and exhibit potential anti-hyperglycemic and anti-adipogenic activity.